Creation of a high-yielding recombinant maize hybrid for the production of a microbicide to prevent HIV-1 transmission - Eugenia Barros; Sydney Nelson (South African Journal of Science)
The aim of this study was to use conventional breeding to increase the production in maize of the human monoclonal antibody 2G12, known to have potential therapeutic properties in the prevention of HIV-1 transmission. The recombinant antibody, together with a fluorescent marker, was introduced into two South African high-performing maize elite inbred lines by crossing them with a transgenic maize line that had been transformed with the monoclonal antibody 2G12. The effect of breeding to produce high-expressing recombinant hybrid seed was evaluated by comparing 2G12 production in the different breeding lines with the original maize line. 'Good production practice standards' were followed throughout the breeding programme. 'Conventional drug regulations' adapted to plant- made pharmaceuticals were also followed, with the seeds being stored in a 'master seed bank'. The maize hybrid expressed a higher level of the antibody than the recombinant maize elite lines. This plant-derived antibody provides a means of producing a microbicide component that could be used with other HIV-neutralising antibodies as an additional approach to prevent HIV infection.